Preliminary assessment on cocrystals of nicotinamide:cinnamic acid and nicotinamide:p-coumaric acid at different solvents and ratio / Mohamad Nor Amirul Azhar Kamis - Kamis, Mohamad Nor Amirul Azhar; Mohd Zaki, Hamizah; Anuar, Nornizar Anuar; Jalil, Mohammad Noor (Faculty of Applied Sciences, 2021)
Cocrystal plays an important role in the pharmaceutical industry to improve the low solubility and bioavailability of drugs. In this study, the cocrystal formation screening was carried out for nicotinamide(NIC) as the API (Active Pharmaceutical Ingredient) with two coformers; cinnamic acid (CIN), and p-coumaric acid (COU) using recrystallization method with different solvents (methanol, ethanol, and acetonitrile) and molar ratios of NIC:CIN and NIC:COU of 1:1, 1:2 and 2:1. The NIC:CIN and NIC:COU mixtures were characterized using Differential Scanning Calorimetry (DSC), Powder X-ray Diffraction (PXRD), and Fourier Transform Infrared (FTIR) to assess the formation of cocrystal. All characterization data for NIC:CIN mixtures showed that the use of different types of solvents and molar ratios have no significant effect on the formation of the cocrystal. The characterization data showed the formation of similar NIC:CIN cocrystal with no polymorphism with a melting temperature of 96-98 oC for all mixtures. The diffraction pattern of all NIC:CIN also showed similar new peaks at 2θ of 6.7°, 17.7°, 20.6°, 22.4°, and 25.1°. The DSC and PXRD data of NIC:CIN were supported by FTIR which revealed similar hydrogen bonding interaction for all NIC:CIN mixtures. The characterization of NIC:COU mixture revealed four different cocrystal forms with melting points of 118 °C, 152 °C, 160 °C, and 169 °C. The PXRD data of NIC:COU mixture also showed different diffraction patterns signifying distinct crystalline identities which supported with different FTIR spectrum validating the difference in hydrogen bonding interaction. It was observed that the use of different types of solvents did not give significant effects on the formation of NIC:CIN and NIC:COU cocrystals.